Adoption of improved agricultural practices: Learning from off-season vegetable production in Nepal - Raju Ghimire; Marari Suvedi; Michael Kaplowitz (Journal of International Agricultural and Extension Education, 2022)
This study examines factors that appear to contribute to farmers’ adoption and discontinuation of poly house technology for off-season vegetable production. We collected cross-sectional survey data from a sample of 151 households in Kaski district, Nepal during October 2018. The data are analyzed using Heckman’s two stage sample selection model. The study reveals that the family members report being engaged in nonfarm sector that there is an increased probability of discontinuation of poly house technology. Farmers may be diverting their labor towards nonfarm activities that result in higher returns to labor and different risks. At the same time, the results indicate that farmers who did not receive training on vegetable production were more likely to discontinue poly house technology. It was also found that increasing farmers’ engagement with marketing activities increased the likelihood of farmers to continue poly house technology and increase household income. The provision of continued technical support (e.g., training), input supply (e.g., seeds, fertilizers) and market information are essential to sustain the adopted technologies. The study sheds light on the sustainability of technology adoption by underpinning the importance of extension services for longer-term adoption. We believe that the combined effect of various technologies would be associated with sustained adoption of the improved off-season technologies. This provides a new direction to operationalize farmer-oriented policies in agricultural extension and helps in devising programs for sustained adoption of technology.
Keywords: Technology adoption; Off-season vegetables; Poly house; Sustainability; Farm income; Nepal